Pendampingan UMKM Keripik Wulan 008 di Desa Panimbang Jaya: Inovasi Produk, Branding, Digitalisasi Pemasaran, Pencatatan Keuangan, dan Pengajuan Bantuan Mesin Produksi - Wiwi Sulandari; Gagah Dwiki Putra Aryono; Andika Purnama; Abdul Kohar; Rizqi Ardiansyah (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service program aims to empower UMKM Keripik Wulan 008 in Panimbang Jaya Village through a series of activities focusing on business capacity enhancement. The program was initiated to address challenges faced by the business, such as limited product innovation, lack of branding, insufficient digital marketing strategies, and suboptimal financial management. To overcome these issues, the program adopted a participatory approach consisting of several stages: field observation to identify core problems, training sessions to improve knowledge, workshops for practical application, and direct mentoring to ensure implementation. Key activities included product innovation by introducing new flavor variants and designing more attractive packaging, strengthening brand identity through the creation of professional logos and labels, and expanding marketing reach via social media and marketplace platforms. Additionally, Excel-based financial recording training was provided to simplify cash flow monitoring and basic financial reporting. The team also assisted in preparing a proposal for production equipment support to increase production capacity. Evaluation results demonstrated significant improvements in product quality, stronger brand identity, and more modern and effective marketing strategies. Overall, this program has proven to be effective in enhancing the competitiveness of UMKM Keripik Wulan 008 and is expected to serve as a sustainable empowerment model for small businesses, thereby contributing to local economic development.